Inclusive economic growth based on the digital transformation of regions - Zokirova Bakhora Zakir kyzy (THE INNOVATION ECONOMY, 2026)
This article analyzes the process of digital transformation of regions and its impact on inclusive economic growth. It highlights the opportunities of digital technologies in enhancing efficiency, transparency, and equity across territories. At the same time, the study identifies key challenges such as infrastructure gaps, lack of skilled human resources, and the digital divide. Based on international experience, relevant conclusions are drawn for Uzbekistan’s regional development.